EVALUASI EFEKTIVITAS DEKLARASI PANMUNJOM DALAM PROSES DENUKLIRISASI SEMENANJUNG KOREA - Brigitha Leovani Pailo; Agussalim Burhanuddin (PARADIGM : Journal Of Multidisciplinary Research and Innovation, 2024)
This study evaluates the Panmunjom Declaration's effectiveness in the Korean Peninsula's denuclearization process. This study uses a qualitative approach with an analysis of literature and case studies to assess the achievements, challenges, and implications of the existence of the Panmunjom Declaration, as well as the data collection method and type of secondary data used. The Panmunjom Declaration, signed on 27 April 2018 by the leaders of North and South Korea, pledges to work together towards peace, stability, and complete denuclearization in the region. The results show that while the Panmunjom Declaration created positive momentum for dialogue and reduced tensions on the Korean Peninsula, progress on denuclearization has been limited. This study highlights the complexity of security, political, and economic dynamics in the Korean Peninsula region. Major obstacles include lack of trust, divergent strategic interests, and international political dynamics. The study concludes that the Panmunjom Declaration requires more concrete and comprehensive efforts to achieve its ultimate goal. Policy recommendations, including increased multilateral diplomacy, are expected to encourage North Korea's commitment to denuclearization.